Reverse radial forearm perforator plus flaps for the reconstruction of postelectrical burn sequelae of hand and forearm defects - Pradeoth Mukundan Korambayil; Prashanth Varkey Ambookan; Vinoth Kumar Dilliraj; Rameela Ravindran Karangath (Wolters Kluwer Medknow Publications, 2019)
Background: The reverse radial forearm perforator flaps are useful in softtissue reconstruction of the hand and forearm. Certain modifications in the flap and usage of hyperbaric oxygen therapy as an adjunct in reconstruction could aid in better outcome of the surgical procedure. The conventional reverse radial artery forearm flap incorporates the radial artery along with its venae commitants along with the flap providing less chances of venous congestion. The per-foratoronly flap may cause a twist in a pedicle which may not affect the artery much, but a small increase in pressure may obstruct the tiny veins running along with the perforator resulting in chances of venous congestion which is a common problem in propeller or perforator flaps. This can be overcome by designing a flap with adequate venous outflow and reducing the postoperative inflammatory edema to prevent pressure to the tiny perforators with arterial and venous components. Aims and Objectives: To focus on flap harvest in a perforator plus model to increase the venous outflow and use of hyperbaric oxygen therapy as an adjunct to prevent the inflammatory edema on the perforator vessels. Materials and Methods: Reverse radial artery perforator plus flaps used for the reconstruction of hand and forearm soft-tissue loss in a series of patients due to electrical burns. We used hyperbaric oxygen therapy as an adjunct for reconstruction. Results: No flap related complication in the series. One patient developed venous congestion at the distal tip region which settled without any further intervention. Conclusion: Defects of the hand and forearm due to the electrical burns could be effectively managed with radial forearm perforator plus flap with allowing adequate venous outflow, and hyperbaric oxygen therapy as an adjunct in electrical burns.